IGARSS 2019 - 2019 IEEE International Geoscience and Remote Sensing Symposium 2019
DOI: 10.1109/igarss.2019.8900354
|View full text |Cite
|
Sign up to set email alerts
|

Eelgrass Beds and Oyster Farming in a Lagoon Before and After The Great East Japan Earthquake of 2011: Potential for Applying Deep Learning at a Coastal Area

Abstract: There is a small number of case studies of automatic land cover classification on the coastal area. Here, I test extraction of seagrass beds, sandy area, oyster farming rafts at Mangoku-ura Lagoon, Miyagi, Japan by comparing manual tracing, simple image segmentation, and image transformation using deep learning. The result was used to extract the changes before and after the earthquake and tsunami. The output resolution was best in the image transformation method, which showed more than 69% accuracy for vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Conducting up‐to‐date statistical analyses of their changes from the past in marine biodiversity should be readily evaluated in this region where marine ecosystem is rapidly changing with economic developments and global climate changes. Moreover, AP‐MBON intends to promote following research and outreaching activities such as; (a) Continuing monitoring of marine biodiversity in the AP region (including citizen science programs) in a globally‐coordinated programs such as Reef Life Survey (Edgar et al, 2017), Reef Check (Chelliah et al, 2015), Seagrass Watch (McKenzie et al, 2000) and Global Ocean Observing System (GOOS), (b) Analyzing broad‐scale, long‐term changes in marine biodiversity in AP Region using global databases such as OBIS and GBIF; (c) Supporting design and adaptive governance of marine protected areas based on scientific data on marine biodiversity (Yamakita et al, 2015; Yamakita et al, 2017); (d) Analyzing values of ecosystem services, its trends, and its linkage to human society by social‐ecological studies (Nakaoka et al, 2018); (e) Developing and apply cross cutting‐edge technologies to marine biodiversity research such as meta‐barcoding/environmental DNA (eDNA) (Miya et al, 2015), and remote sensing/GIS/Deep learning technologies (Yamakita, 2019; Yamakita, Sodeyama, Whanpetch, Watanabe, & Nakaoka, 2019); (f) Outreach of scientific outputs to various types of stakeholders of marine biodiversity and developing sustainable management plans via codesign, coproduction and co‐delivery (Yamakita, 2019; Yamakita et al, 2019).…”
Section: New Strategic Plans: To 2030 and Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…Conducting up‐to‐date statistical analyses of their changes from the past in marine biodiversity should be readily evaluated in this region where marine ecosystem is rapidly changing with economic developments and global climate changes. Moreover, AP‐MBON intends to promote following research and outreaching activities such as; (a) Continuing monitoring of marine biodiversity in the AP region (including citizen science programs) in a globally‐coordinated programs such as Reef Life Survey (Edgar et al, 2017), Reef Check (Chelliah et al, 2015), Seagrass Watch (McKenzie et al, 2000) and Global Ocean Observing System (GOOS), (b) Analyzing broad‐scale, long‐term changes in marine biodiversity in AP Region using global databases such as OBIS and GBIF; (c) Supporting design and adaptive governance of marine protected areas based on scientific data on marine biodiversity (Yamakita et al, 2015; Yamakita et al, 2017); (d) Analyzing values of ecosystem services, its trends, and its linkage to human society by social‐ecological studies (Nakaoka et al, 2018); (e) Developing and apply cross cutting‐edge technologies to marine biodiversity research such as meta‐barcoding/environmental DNA (eDNA) (Miya et al, 2015), and remote sensing/GIS/Deep learning technologies (Yamakita, 2019; Yamakita, Sodeyama, Whanpetch, Watanabe, & Nakaoka, 2019); (f) Outreach of scientific outputs to various types of stakeholders of marine biodiversity and developing sustainable management plans via codesign, coproduction and co‐delivery (Yamakita, 2019; Yamakita et al, 2019).…”
Section: New Strategic Plans: To 2030 and Beyondmentioning
confidence: 99%
“…The 3D modeling and CT scanned data would also contribute to the development of morphology and taxonomy (see recent data in “ffish‐asia”; Kano et al, 2013, Table 1). Image recognition and analysis is also essential for biodiversity monitoring by deep/machine learning (e.g., satellite map, Samasse, Hanan, Anchang, & Diallo, 2020; seagrass, Yamakita, 2019). In addition, data representation techniques such as online dashboard are also expected for more efficient use of the data.…”
Section: New Strategic Plans: To 2030 and Beyondmentioning
confidence: 99%
“…Deep learning methods have gained popularity for coping with the generalization problem owing to their advantages in digging semantic values after convolution. For example, Yamakita et al [21] confirmed that a deep convolutional generative adversarial network showed better results than the fully convolutional network for classifying different objects, including seagrass, by using aerial and satellite images (QuickBird). However, the deep convolutional generative adversarial network may exhibit limitations, such as collapsing generators, and is highly sensitive to hyper-parameter selections [22].…”
Section: Introductionmentioning
confidence: 99%
“…the target image). Although the generator and discriminator use a kind of convolutional neural network that is the basic model of deep learning, cGAN shows higher accuracy in image recognition than other conventional machine learning methods, including supervised classification and other simpler deep learning methods (Goodfellow et al 2016, Creswell et al 2018, Yamakita 2018, 2019. cGAN was not specifically developed for remote sensing, but the model has been applied to automatic map production from satellite images (Isola et al 2016).…”
Section: Introductionmentioning
confidence: 99%